THE BEGINNING OF THE POLICY OF PERESTROIKA IN THE USSR - Abuev Khusan Odilovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article describes the socio-political processes of the last years of the Soviet regime. The main causes of the socio-economic crisis are listed here.